The legend of the golden snail - Base, Graeme (Australia : Penguin random house, 2019)
Inspired by the tale of a magical Golden Snail banished to the Ends of the Earth by a Grand Enchanter, a young boy named Wilbur sets out on a daring voyage to find the legendary snail and claim it as his own. Along the way he encounters strange creatures and overcomes many challenges. Finally he reaches the Ends of the Earth, but what he finds there is not quite as he imagined.
Keywords: English - Fiction; Magic Children's picture book